AGRICULTURAL TRENDS IN ROMANIA IN THE CONTEXT OF THE CURRENT TRENDS OF THE WORLD ECONOMY - Nicoleta MATEOC-SÎRB; Cristina-Viorica BACĂU; Anișoara DUMA COPCEA; Teodor MATEOC-SÎRB; Camelia MĂNESCU; Simona NIȚĂ; Oana SICOE-MURG; Gabriel SUSTER (Journal of Applied Life Sciences and Environment)
The role of agriculture is an extremely important one because it provides the necessary production of foods for the population and, at the same time, represents a source of raw materials for different processing industries. For a growing population, agriculture has been the main source of agri-food products that must ensure the food security of the population. Compared to other states of Europe, Romania is one of the European countries with the most favourable soil and climate conditions for agriculture. The last world crises, from the crisis in 2008 to the pandemic crisis in 2020-2021, and especially to the current conflict between Russia and the Ukraine, have brought up the issue of food self-sufficiency. During the current period, it is important to know what production can be obtained in Romanian agriculture and if it can provide the food necessary for the population. An analysis regarding the dynamics of the cultivated areas and production of the main crops in Romania has been carried out, for each of its 8 development regions. The data, collected from different sources, were analysed using different methods. The research results highlight, for example, that Romania can easily achieve the self-sufficiency stage for most agricultural products of plant origin. In conclusion, natural resources, as well as the existence of a certain material base in Romanian agriculture, can ensure the increase of agricultural production, the satisfaction of the food needs of the population, as well as a certain availability for export.